The role of destination marketing in enhancing local perceptions of Djelfa Province - Algeria from the perspective of its residents - Dahmane, Ahmed (The International tax journal, 2025)
This study aimed to explore the role of destination marketing in enhancing local perceptions of Djelfa Province in Algeria from the viewpoint of its residents. A descriptive and analytical methodology was used, with a random sample of 150 individuals from which 127 valid questionnaires were recovered for analysis. The study focused on understanding concepts related to the elements of the tourism marketing mix, investigating the impact of this mix on the perceptions and tourism image of the province, and identifying the most influential elements of the mix on the image. Results indicated that the distribution element had the highest mean approval (3.56), reflecting its significant role in shaping the tourism image, while the physical environment received the lowest acceptance score, indicating a need for improvements. The tourism image of the province from the residents’ perspective was moderate, with a mean score of 3.24. Analyses showed a statistically significant correlation between the tourism marketing mix and the tourism image, explaining 13.4% of the variance, with the tourism product having a positive significant effect on the image, whereas factors such as pricing, distribution, promotion, service provider performance, the physical environment, and service delivery process had no significant effects.